Hearing threshold of patients with chronic kidney disease undergoing haemodialysis - Fufore, Mohammed Bello; Kirfi, Abdullahi Musa; Salisu, Abubakar Danjuma; Samdi, Musa Thomas; Abubakar, Abdulhameed Bala; Onakoya, Paul Adekunle (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Chronic kidney disease (CKD) has been recognised as a serious public health issue due to its many associated complications, including hearing loss (HL). The study aimed to determine the hearing threshold of adult patients with CKD undergoing haemodialysis. Methods: This was a prospective, hospital-based study of patients with CKD undergoing haemodialysis in a tertiary hospital in Kaduna, carried out between December 2017 and November 2018. Ethical approval and informed consent were obtained. Data was analysed using SPSS version 20. Statistical analysis was with t test and Chi square and level of significance was set at p<0.05. Results: Thirty patients with CKD undergoing haemodialysis were age and sex matched with 30 controls (CKD patients not on dialysis). Mean age for subjects and controls were 44.6±14.3 and 41.7±12.5, respectively. Mean right ear pure tone average (PTAv) among subjects and the controls were 32.7±9.6 and 25.6±6.2, respectively. Mean left ear PTAv among subjects and controls were 33.3±9.7 and 25.8±6.2, respectively. Hearing loss was present in 73.3% and 41.7% among the subjects and controls respectively (p<0.001). Of the 22 ears of subjects that had ≤10 sessions of dialysis, 13 (59.1%) ears had HL and of the 38 ears that had >10 sessions of dialysis, 30 (78.9%) ears had HL. The difference between hearing threshold and sessions of dialysis was statistically significant (p=0.001). Conclusions: Hearing thresholds of CKD patients on dialysis was higher than those not on dialysis. Haemodialysis significantly affects the hearing thresholds of CKD patients.